2015
DOI: 10.3389/fpls.2015.00556
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase cascades in Vitis vinifera

Abstract: Protein phosphorylation is one of the most important mechanisms to control cellular functions in response to external and endogenous signals. Mitogen-activated protein kinases (MAPK) are universal signaling molecules in eukaryotes that mediate the intracellular transmission of extracellular signals resulting in the induction of appropriate cellular responses. MAPK cascades are composed of four protein kinase modules: MAPKKK kinases (MAPKKKKs), MAPKK kinases (MAPKKKs), MAPK kinases (MAPKKs), and MAPKs. In plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 95 publications
(157 reference statements)
1
64
0
Order By: Relevance
“…There are only 12 MAPK and 7 MAPKK members in the strawberry genome, while at least 20 MAPK genes and 10 MAPKK genes have been identified in the A. thaliana genome, even though the genome size of F. vesca (240 Mb) is approximately twice that of the A. thaliana genome (~125 Mb). The numbers are more comparable to those in V. vinifera (~400 Mb), where 14 MAPK and 5 MAPKK members have been identified [ 1 , 42 ]. With 73 members, the MAPKKK subfamily is similar in size to that of rice (75 members), larger than that of grapevine (62 members) but smaller than that of A. thaliana (80 members).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…There are only 12 MAPK and 7 MAPKK members in the strawberry genome, while at least 20 MAPK genes and 10 MAPKK genes have been identified in the A. thaliana genome, even though the genome size of F. vesca (240 Mb) is approximately twice that of the A. thaliana genome (~125 Mb). The numbers are more comparable to those in V. vinifera (~400 Mb), where 14 MAPK and 5 MAPKK members have been identified [ 1 , 42 ]. With 73 members, the MAPKKK subfamily is similar in size to that of rice (75 members), larger than that of grapevine (62 members) but smaller than that of A. thaliana (80 members).…”
Section: Discussionmentioning
confidence: 61%
“…It is interesting that no FvMAPKKK was found that belonged to the ZIK subfamily, which in other species has members with a conserved GTPEFMAPE (L/V) Y signature. The absence of the characteristic ZIK subfamily feature in F. vesca might suggest the presence of a slightly modified RAF domain, instead of the typical ZIK domain as reported in Vitis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, analyses of exon-intron junctions and of the intron phase inside the predicted coding region of each candidate gene revealed high levels of conservation within and between phylogenetic groups. These analyses demonstrated the existence of 14 MAPKs, five MAPKKs, 62 MAPKKKs, and seven MAPKKKKs in Vitis vinifera [26] and cucumber (Cucumis sativus L.). In Cucurbitaceae crops, which are highly susceptible to environmental stress and pathogen attack, analyses demonstrated the presence of at least 14 MAPKs, six MAPKKs, and 59 MAPKKKs [6].…”
Section: Reactive Oxygen Species Metabolism and Senescencementioning
confidence: 86%
“…MAPK cascades have been found in all eukaryotes [ 3 ]. For example, the grape ( Vitis vinifera ) genome possesses 88 MAPK cascade genes, including 7 MAPK kinase kinase kinases (MAPKKKKs), 62 MAPKKKs, 5 MAPKKs, and 14 MPKs [ 4 ]. The Arabidopsis ( Arabidopsis thaliana ) genome encodes 80 MAPKKKs, 10 MAPKKs, and 20 MPKs [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%